HyperSHArc: Single-Isocenter Stereotactic Radiosurgery of Multiple Brain Metastases Using Proton, Helium, and Carbon Ion Arc Therapy - Lennart Volz, PhD; Peilin Liu, MSc; Thomas Tessonnier, PhD; Xiaoda Cong, MSc; Marco Durante, PhD; Andrea Mairani, PhD; Wenbo Gu, PhD; Amir Abdollahi, MD, PhD; Xuanfeng Ding, PhD; Christian Graeff, PhD; Taoran Li, PhD; Stewart Mein, PhD (Advances in Radiation Oncology)
Purpose: This work presents a proof-of-concept study of HyperSHArc, spot-scanning hadron arc (SHArc) therapy for single-isocenter stereotactic radiosurgery of multiple brain metastases (MBMs). HyperSHArc plans using proton, helium, and carbon ions were compared with state-of-the-art volumetric modulated photon arc therapy. Methods and Materials: Treatment design and optimization procedures were devised using commercial and in-house treatment planning systems. Planning and delivery methods considered dedicated energy, spot, and multiarc selection strategies. Proton, helium, and carbon HyperSHArc plans were generated for patients with MBM exhibiting 3 to 11 intracranial lesions with gross tumor volumes (GTVs) between 0.03 and 19.8 cc, at prescribed doses between 19 and 21Gy in a single-fraction. Planning target volumes (PTVs) considered a 1-mm isotropic margin around the GTV, and robust optimization with 2.5%/1 mm criteria for range and position uncertainty was applied. Photon hyper-arc volumetric modulated arc therapy (HA-VMAT) plans were optimized for the PTVs using the HyperArc® single-isocenter stereotactic radiosurgery platform (Varian, Palo Alto, CA, USA). Results: HyperSHArc plans were comparable between particle species, achieving highly conformal target doses and satisfying clinical coverage criteria. Particle arc plans reduced V2Gy and V4Gy in the healthy brain compared with HA-VMAT, while intermediate doses (V8Gy-V16Gy) were similar or reduced depending on the number of lesions. Particularly for the case with 11 targets, a considerable reduction in V12Gy was observed that could be relevant for reducing the risk of treatment-induced radionecrosis. HyperSHArc using carbon ions boosted dose-averaged linear energy transfer inside the target relevant to overcoming radioresistance factors (>100 keV/μm). Conclusions: We present the first particle arc therapy strategies for MBM. Results demonstrate that with HyperSHArc, dose conformity comparable or superior to HA-VMAT is achievable while reducing the low-dose bath and increasing mean dose-averaged linear energy transfer in the GTV. Our findings suggest that HyperSHArc using light and heavy ions could be an effective and efficient means of treating MBM. Further development of HyperSHArc optimization and delivery is justified.